ANALISA KESEHATAN BANK - Muhammad Ardi; Mutiyah Mahdin (Jurnal Akuntansi dan Keuangan Syariah (Jurnal Akunsyah), 2021)
This paper aims to determine the  bank financial statements in terms of bank liquidity which is one of the most important media for assessing the economic condition of banks regarding the cash position of a bank and the ability of banks to meet short-term needs (debt) on time.The method used in this article is descriptive method with  library research, such as  several sources of books, figures and  formulas. Liquidity management is one of the most important functions carried out by banking institutions. An efficient management needs instruments and financial market  both short term and long term whether  conventional and sharia banking with the CAMEL approach. It is easy to identify the bank if the bank condition reaches a ratio scale healthy (19%-0%) with predicate 81-100, moderate (24%-19,1%) with predicate 66-81, less healthy (49%- 34.1%) with predicate 51-66 and unhealthy (100%-49%) with predicate 0-51.